PNEUMOCOCCAL INFECTION. IMMUNIZATION BY A 7-VALENT CONJUGATED PNEUMOCOCCAL VACCINE OF CHILDREN BORN TO HIV-POSITIVE WOMEN - L.Yu Afoninа; E.E. Voronin; Yu.A. Fomin; Yu.V. Lobzin (Вопросы современной педиатрии)
The article contains pneumococcal infection prevalence survey among HIV-positive children. Questions of pneumococcal infection prevention using pneumococcal conjugated vaccine are discussed in the article. Recommendations upon immunization of HIV-positive children and children born to HIV-positive women against pneumococcal infection are given in the article as well.Key words: children, HIV-infection, pneumococcal infection, pneumococcal conjugated vaccine.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2011; 10 (4): 36–40)